Community Based Tourism in Increasing the Competitiveness of MSMEs: Integration of Islamic Business Ethics in Komodo Tourist Destinations - Mukhlishin; Fathurrohman Husen (Mabsya: Jurnal Manajemen Bisnis Syariah, 2025)
Community-based tourism has emerged as a key strategy for enhancing the economic welfare of local communities, particularly in Komodo Village, which is evolving into a prominent tourist destination. This study aims to analyze the optimization of tourism management in Komodo Village and its role in increasing the income of local MSMEs (Micro, Small, and Medium Enterprises) by evaluating the integration of Islamic business ethics into local economic practices. A qualitative approach was employed, including in-depth interviews with MSME actors, tourism managers, and tourists, along with direct observations of the economic dynamics in Komodo Village. Tourism in Komodo Village has significantly contributed to the growth of MSMEs and diversification of local livelihoods. However, challenges such as limited infrastructure, fluctuations in tourist numbers, and business practices not fully adhering to Islamic principles of justice were identified. Despite these issues, there is a growing awareness among the community about the importance of integrating Islamic values into business practices. The findings suggest that halal tourism and the Islamic economy offer a more inclusive and sustainable model for tourism development. There is a need for more integrated policies in halal tourism management and strategies aimed at strengthening MSMEs to enhance the economic competitiveness of the local community.